"At-Home" Photobiomodulation: A New Approach for Bell's Palsy Treatment. (14th September 2021) - Fornaini, Carlo; Meng, Zhao; Merigo, Elisabetta; Rocca, Jean-Paul
Abstract : Objective . This report is the first one to describe the possibility to use "self‐administered" photobiomodulation (PBM) for Bell's palsy (BP) treatment. Background . BP is a peripheral disorder of the facial nerve causing sudden paralysis of unilateral facial muscles, and PBM has been successfully suggested for its treatment without any side effect. This is the first case report where a laser device was successfully used at home by the patient herself to treat BP opening new perspectives on the therapy of this disease. Methods . This report describes the "at-home PBM" treatment performed on a 15-year-old girl who presented BP consisting of acute pain on the right side of her face, difficulty in biting and dripping saliva from the right side of her lips. The treatment was performed twice a day by cutaneous applications, each of 15 minutes (total fluence 48 J/cm 2 ) in an area corresponding to the parotid gland by a device emitting at 808 nm at 250 mW output power. Results . Two weeks after PBM treatment, performed at home twice a day by the patient herself without any kind of pharmacological therapy, the complete disappearing of the disease was noticed with no side effects. Conclusion . With the limitations due to a single case report and with the need of further clinical trials to confirm it, "at-home PBM" seems to represent a good and safe approach to the treatment of BP.